Review of ITF-approved Player Analysis Technology (PAT) - Vaquer Castillo, A. (Coaching and Sport Science Review, 2023)
In this article an instrumental review is carried out from a technical/tactical point of view of measuring devices and apparatus applied to tennis. More specifically, a review of the current panorama of the "Player Analysis Technology" (PAT) approved by the ITF (International Tennis Federation) is proposed. The rationale would be the growing importance and application that they are acquiring since the approval of rule 31 by the ITF that allows the use of these PATs in tournaments.